Exploring Factors Related to Burnout among Special Education Teachers in Specialized Schools - Huk, Oksana; Cesario, Brian (Journal of the American Academy of Special Education Professionals, 2020)
The purpose of this initial exploratory research was to examine the extent to which burnout and turnover among special education teachers working within specialized schools were related to student maladaptive behavior (aggressive behaviors, self-injurious behaviors, and stereotypic behaviors), workplace support (from administration and colleagues), and teacher irrational beliefs. Correlational analyses indicated that all forms of student maladaptive behavior, administrative support, teacher irrational beliefs (low frustration tolerance and attitudes toward the school) were significantly related to burnout. Student self-injurious behavior and low frustration tolerance were significantly related to turnover. Teacher burnout and teacher turnover were also significantly positively correlated. Colleague support, self-downing, and authoritarian attitudes toward students were unrelated to burnout or turnover. Furthermore, no association was found between turnover and student aggression, student stereotypical behavior, and support from administration.